Mixed-Method Heat Acclimation Induces Heat Adaptations in International Triathletes Without Training Modification - Carl A. James; Ashley G. B. Willmott; C. W. Daniel Lee; T. K. Gabriel Pun; Ray Tai; Oliver R. Gibson (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships. Methods Six international triathletes completed 8 pre-competition HA sessions (5 active: running/cycling, 3 passive: hot water immersion [HWI]), across 2-weeks. Outdoor high-intensity training sessions were followed by 30–60 min HWI, whilst low-intensity cycling/running sessions were completed in a hot, humid environmental chamber. To assess heat adaptations, participants completed three 25 min heat stress tests (HST) involving iso-speed treadmill running (session 1 = HST1, session 5 = HST2, and session 8 = HST3). Physiological, haematological and wellbeing monitoring were conducted throughout HA. Results Reduced heart rate (~ − 6 beats/min) was observed within HST3 ( P = 0.01, η p 2 = 0.64), versus HST1 and HST2. No changes in core temperature were observed across HSTs ( P = 0.055 , η p 2 = 0.44). Sweat sodium concentration was lower by HST2 at the arm (− 23 ± 16 mmol/L, P = 0.02) and back (− 27 ± 17 mmol/L, P = 0.01). White blood cell count reduced from baseline to the end of HA ( P = 0.02, η p 2 = 0.27), but no changes were found in any other haematological markers (all P > 0.05). Perceptual wellbeing measures did not change across HA (all P > 0.05). Conclusion By HST3, seven prior mixed-method HA sessions improved markers of heat adaptation (exercising HR and sweat concentration) within international triathletes. Mixed-method HA may be implemented without modifying training load, with no apparent detrimental effects on athlete health or training stress markers.

Analysis and Potential Alternatives for the Disputed South China Sea from Ocean Governance in the Polar Regions - Ray Tsung-Han Tai; Nathaniel S. Pearre; Shih-Ming Kao (Coastal Management, 2015)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)